Emission Characteristics and Health Risk Assessment of Volatile Organic Compounds in Key Industries: A Case Study in the Central Plains of China - Fengwei Liu; Lei Tong; Qingyue Luo; Yufei Ling; Hongyi Gu; Yangchao Lv; Anwei Shi; Hui Liu; Hang Xiao; Cenyan Huang (Atmosphere)
Volatile organic compounds (VOCs), the precursors of ozone and fine particulate matter, are one of the atmospheric pollutants harmful to human health. The emission characteristics of VOCs in Anyang, a typical industrial city in the Central Plains of China, are unclear. To determine the emission level and composition of local VOCs, this study conducted on-site sampling of 20 factories in eight key industries. A total of 105 VOC species in seven categories were observed. The concentration of total VOCs emitted from the eight industries in order from large to small was as follows: packaging and printing > pharmaceutical > paint manufacturing > industrial coating > chemical industry > metal smelting > furniture manufacturing > textile printing and dyeing. In addition to industrial coating, the total VOCs and their corresponding ozone formation potential of organized emissions in seven industries (1.44–87.64, 1.52–181.61 mg/m3) were higher than those of unorganized emissions (0.38–24.17, 0.38–125.55 mg/m3). The VOC emissions were concentrated in the central, south-central, and south-eastern parts of the city, mainly from the factories in the packaging and printing, pharmaceutical, paint, and coating industries. The furniture manufacturing (4.55 × 10−3) and pharmaceutical (1.66 × 10−3) industries in organized emissions were at high risk of carcinogenesis, while the pharmaceutical industry in unorganized emissions (3.61 × 10−4) was at moderate risk of carcinogenesis. Naphthalene was the main high-risk compound. In terms of non-carcinogenic risk, the packaging and printing industry in organized emissions (228.51) and the metal smelting industry in unorganized emissions (16.16) had the highest risk, and the main high-risk compound was ethyl acetate.